THE INDEX EVALUATION OF PHYSICAL DEVELOPMENT BY RURAL STUDENTS - Валентина Сергеевна Гладкая; Вера Людвиговна Грицинская (The Publishing House Medicine and Enlightenment, 2017)
The aim of the exploration was to reveal the peculiarities of physical development of rural students living in the southern districts of the Krasnoyarsk territory. There were surveyed 304 pupils (157 boys and 147 girls) aged 7 to 18 years living in rural settlements of the South of Krasnoyarsk territory. The examination included somatometry's conduct and evaluation of the physical development of students with the use of the index: the weight and growth Ketle2 (BMI), «walling» Verveka-Vorontsov, the ratio of waist circumference and body length. High prevalence of disharmonic physical development options, due to a deficiency and excess body weight. Of the students surveyed 11,5 % of boys and 6,1 % of girls are need in-depth survey in order to verify the diagnosis of obesity. With age there is a decrease the number of children with a harmonious relation of the linear and lateral growth processes. More children who have cross-body speed growth process prevail over increase in the longitudinal dimensions among the high school students. Given these results, it is necessary to analyze the adverse factors in the subsequent development of the preventive measures.